Penanaman Nilai Kearifan Lokal pada Peserta Didik Melalui Pendidikan Multikultular - Irman Syarif; Muhidin Abuamar Ratuloly (heritage, 2020)
Abstract This study aims to find out the value of local wisdom in students and what factors influence the difference in local wisdom based on multikultular in elementary school.  This research method is a qualitative description, data collection techniques are observation, interview and documentation. Data analysis starts from data collection, data reduction, withdrawal of conclusions.The results showed that local wisdom is embedded in elementary school students through formal and nonformal learning, formal learning includes daily teaching activities from 07:30-13:00 while nonformal learning includes extracurricular activities in the form of olaraga practice, dance, music and habituation of living together in the school environment. Fostering local wisdom in elementary school through learning activities teaching the learning process emphasizes on optimizing the role of rationality for students, practice and habituation of dissent. The factors that influence multicultural-based local wisdom differences in elementary schools are the diversity of students who have a wide range of religious differences, social status, gender, ability, age and race, and the collaboration of students in participating in sports and arts events. Abstrak Penelitian ini bertujuan mengetahui nilai kearifan lokal pada peserta didik dan faktor apa saja mempengaruhi perbedaan kearifan lokal berbasis multikultular di Sekolah Dasar.  Metode penelitian ini adalah deskripsi kualitatif, teknik pengumpulan data adalah observasi, wawancara dan dokumentasi. Analisis data dimulai dari pengumpulan data, reduksi data, penarikan kesimpulan. Hasil penelitian menunjukkan bahwa  kearifan lokal yang tertanam pada peserta didik Sekolah Dasar  melalui pembelajaran formal dan nonformal, pembelajaran formal meliputi kegiatan belajar mengajar setiap hari dari jam 07:30-13:00 sedangkan pembelajaran nonformal meliputi ekstrakurikuler berupa latihan olaraga, tarian, musik dan pembiasaan hidup bersama di lingkungan sekolah. Penumbuhkan kearifan lokal di Sekolah Dasar dilakukan melalui proses pembelajaran yang menekankan pada optimalisasi peran rasionalitas bagi siswa, praktek dan pembiasaan perbedaan pendapat. Fakor-faktor yang mempengaruhi perbedaan kearifan lokal berbasis multikultural di Sekolah Dasar  adalah keberagaman siswa karena memiliki berbagai macam perbedaan, yaitu, perbedaan agama, status sosial, dan ras, serta pengelaborasian peserta didik dalam mengikuti lomba olahraga dan seni. Kata kunci: kearifan lokal, pendidikan multikultural